Pengaruh Kompos dan Mulsa Alang-Alang (Imperata cylindrica L.)terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max L.) - Ramah Rosnita Zega; Idwar Idwar; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Soybean (Glycine max L.) is a food commodity that is used as a source of vegetable protein or as an industrial raw material and needs to be increased by using efficient and appropriate cultivation techniques, namely by using compost and giving mulch. This study aims to determine the main effects of compost and mulch of reed as well as their interaction with the growth and production of soybean plants. The research was conducted at the Faculty of Agriculture Experimental Garden, University of Riau from February to May 2018,the experimentally using a randomized block design (RBD), which consisted of two factors, namely the first factor in reed compost (without reed compost, reeds compost 2,5 ton.ha–1 and reeds compost 5 ton.ha-1), second factor reeds mulch (without reed mulch, reeds mulch 10 ton.ha-1 and reeds mulch 20 ton.ha–1). Parameters observed were soil properties, number of individual weeds, plant height, number of primary branches, age of flowering, total pods per plant, percentage of pithy pods, harvest age, seed weight per plot, yield per m2 and weight of 100 seeds. Thedata obtained were analyzed statistically by analysis of variance and were tested further with multiple distance tests at the level of 5%.The results showed that the factors of reed compost 5 ton.ha-1 and reeds mulch 10 ton.ha-1 gave better results for all observational parameters. Giving reeds compost 5 ton.ha-1 with reeds mulch 10 ton.ha-1 is the best combination of all parameters observed in soybean plants and produce seed weight per m2 which is 189,80 grams (1,28 ton.ha-1). Keywords: Compost, Mulch, Reed, Soybeans